THE ROLE OF TELOMERIC PROTEINS AND THEIR RELEVANCE AS TARGETS IN ANTI-CANCER THERAPY - *, Wambua; *, BW; B.O, Olabu (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
The telomere is a region of vital nucleoprotein structures at the terminal end of thechromosome with 500- 3000 repeat sequences of TTAGGG. The shelterin and non-shelterincomplexes are telomere associated proteins. These proteins protect chromosome ends fromfusion and degradation. The non-shelterin complex of proteins is involved in DNA repairwhile the shelterin complex of proteins is responsible for regulating telomere length.Telomerase enzyme lengthens telomeres and in immortal cells it is activated. Approximately90% of human cancers are telomerase positive. The inhibition of telomerase has beenconsidered a safer approach than the use of cytotoxic drugs in anti-cancer therapy. However,the induction of delayed cell growth arrest via telomerase inhibition has been shown to beslow. This is due to the fact that the replication rounds required are too many for it to beeffective. Induction of dissociation of shelterin proteins from telomeric DNA has beenconsidered a more efficacious approach based on gene silencing and mutation studies.The loss of shelterin proteins such as the protection of telomeres 1 (POT 1) and telomererepeat binding factor 2 (TRF 2) in cancer cells has been associated with apoptosis of thetumour cells. Poly ADP ribose polymerase (PARP), a non-shelterin protein, is involved inDNA repair. Drugs such as PJ-34 and 3-Aminobenzamide have been developed as PARPinhibitors. Drugs that dissociate telomeric proteins from telomeric DNA are still underclinical trials, they include Quarfloxin, C-1305 and Telomestatin. These drugs have lowcytotoxicity and are effective against tumours linked with dysfunction of DNA repair. Thelevel of cytotoxicity of a drug is vital in determining its efficacy. The cytotoxicity of cellcycleinhibitors as anti-cancer medication motivated researchers to investigate telomericproteins as targets of anti-cancer intervention. The dissociation of shelterin proteins fromtelomeric DNA and inhibition of non-shelterin proteins such as PARP and Tankyrase 1 and 2have shown promising efficacy levels as anti-cancer therapy.